Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1093/cid/ciab371
|View full text |Cite
|
Sign up to set email alerts
|

Vaccinated and Convalescent Donor–Derived Severe Acute Respiratory Syndrome Coronavirus 2–Specific T Cells as Adoptive Immunotherapy for High-Risk Coronavirus Disease 2019 Patients

Abstract: Background Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) pandemic poses an urgent need for the development of effective therapies for Coronavirus Disease 2019 (COVID-19). Methods We first tested SARS-CoV-2-specific T-cell (CοV-2-ST) immunity and expansion in unexposed donors, COVID-19 infected individuals (convalescent), asymptomatic PCR-positive subjects, vaccinated individuals, non-ICU hospitalized patients a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 40 publications
4
14
0
Order By: Relevance
“…Our observations that T cells can be generated from a small cohort of convalescent individuals to cover a large percentage of the population suggest that the manufacture of a similar repository of SARS-CoV-2-specific T cells is feasible. Other groups have also developed approaches for a T-cell immunotherapy approach to COVID-19 [36][37][38], with the first case report of a heart transplant patient who received SARS-CoV-2 specific T cell therapy recently published [39].…”
Section: Discussionmentioning
confidence: 99%
“…Our observations that T cells can be generated from a small cohort of convalescent individuals to cover a large percentage of the population suggest that the manufacture of a similar repository of SARS-CoV-2-specific T cells is feasible. Other groups have also developed approaches for a T-cell immunotherapy approach to COVID-19 [36][37][38], with the first case report of a heart transplant patient who received SARS-CoV-2 specific T cell therapy recently published [39].…”
Section: Discussionmentioning
confidence: 99%
“…Unstimulated cells were used as negative controls. Following overnight stimulation, cells were surface stained for CD3, CD4, CD8, CD56, CD137 (4B4), CD154 ( 14 21 ), CD25 (BC96), CD38 (HIT2), CD69 (FN50), and HLA-DR (L243). Flow cytometry was performed using the BD Biosciences Fortessa cytometer.…”
Section: Methodsmentioning
confidence: 99%
“…An important issue that remains unresolved thus far is whether these pre-existing cross-reactive T cells will play a protective or pathologic role once the hitherto uninfected host is subsequently exposed to SARS-CoV-2 [ 32 , 33 , 34 ]. In one retrospective study, individuals with recent exposure to endemic human CoV endemic experienced a milder disease course following subsequent SARS-CoV-2 infection, and a subsequent study demonstrated that human CoV specific, SARS-CoV-2 cross-reactive CD4 T cells can be rapidly recruited into the immune response following natural SARS-CoV-2 infection and immunization, while other studies have demonstrated the sub-optimal cytotoxic activity and polyfunctional potential of endemic human CoV derived SARS-CoV-2 cross-reactive T cells [ 35 , 36 , 37 , 65 ]. Carefully designed prospective studies evaluating the clinical outcomes of SARS-CoV-2 infection in SARS-CoV-2 unexposed individuals harboring cross-reactive T cells will be necessary to provide conclusive evidence relating to the protective and/or pathological potential of cross-reactive T cells.…”
Section: T Cell Responses In the Setting Of Sars-cov-2 Infectionmentioning
confidence: 99%
“…Reports have begun to emerge that demonstrate the potential utility of adoptive transfer therapy using ex-vivo expanded SARS-CoV-2 specific T cells [ 37 , 40 , 41 , 42 , 72 , 73 ]. One of the earliest publications in this context utilized a good manufacturing practice (GMP)-compliant methodology to, in vitro, stimulate and expand virus-specific T cells from convalescent donors using SARS-CoV-2 peptides for the purpose of adoptive immunotherapy aimed at immunocompromised patients exposed to SARS-CoV-2 [ 40 ].…”
Section: T Cell Responses In the Setting Of Sars-cov-2 Infectionmentioning
confidence: 99%
See 1 more Smart Citation